Disposable surgical covers for preventing pyogenic postoperative and nosocomial infections - Delikatniy, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article attracts attention of specialists to topicality of disposable surgical covers. Abroad, information about the need for protection of surgical wounds from infections by means of disposable operating clothing and covers (DOCC) appeared as early as in 1970s. «Guidelines for Using DOCC» were developed and accepted for application in the Russian Federation in 2007. The national standard for DOCC was accepted and put into practice in 2010. Disposable surgical covers are manufactured in the Russian Federation following the above standard by enterprises of the association of DOCC manufacturers «Zdravmedtech». Ukrainian enterprise «Zdravmedtech-Chernihiv» is a member of this manufacturers’ association.